Advanced Nitrogen Management: Effects of Nano-Coated Urea on Nitrogen Leaching in Loam - Dinda Mahartian Yunita; M Wasilul Lutfi; Atiqah Aulia Hanuf; Soemarno Soemarno; Sugeng Prijono; Kurniawan Sigit Wicaksono (JOURNAL OF TROPICAL SOILS, 2026)
Urea fertilization using controlled-release techniques is an effective way to reduce nitrogen (N) loss. One technique to decelerate N release and enhance fertilization efficiency involves applying Controlled Release Fertilizer (CRF) via Nano-Coated Urea (NCU) technology. The purpose of this study was to analyze the effect of coated urea application in reducing nitrate leaching rates and improving urea fertilization efficiency in loam soils. The materials used as urea coatings are Bentonite, which has been modified into nanosized particles. The study uses an incubation method with a lysimeter tube and destructive soil sampling to analyze soil nitrate and leached nitrate. The results showed that there was an increase in soil nitrate concentration in the LMC2 treatment (urea coating bentonite) by 28.05% and in the LMC3 treatment (urea coating nano bentonite) by 35.61%, compared to the LMC1 treatment (control urea) of 19.55%.